2019
DOI: 10.1177/0963662519875447
|View full text |Cite
|
Sign up to set email alerts
|

Science journalism for development in the Global South: A systematic literature review of issues and challenges

Abstract: Based primarily on a systematic review of the relevant literature between 2000 and 2017, this article reflects on the state of journalism about science in developing countries, with a focus on its issues, challenges and implications for their developmental processes and causes. Five major themes emerge from our analysis: (a) heavy dependence on foreign sources, especially the media of the Global North; (b) the low status of domestic science news in newsrooms; (c) uncritical science reporting that easily lends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 48 publications
(84 reference statements)
0
25
0
1
Order By: Relevance
“…An international survey of 592 science journalists from all continents found that 43% believed that their role was “to inform”, 23% “to translate complex material”, and 13% “to educate”; less than 10% saw thought their role entailed “mobilising or entertaining the public” or being a “public watchdog” (Bauer et al, 2013b, p. 24). The rare items of scholarship on science journalists in the Global South have generally demonstrated a “scarcity of critical science reporting” (Nguyen et al, 2020, p. 980). Similarly, a survey of more than 60 climate journalists from India, Germany, Switzerland, the US, and the UK identified the presence of a common transnational “interpretive community” in support of the mainstream consensus on anthropogenic climate change and had more traditional self‐perceptions as explainers of a complex phenomenon (Brüggemann & Engesser, 2014), although no similarities or differences between the countries were discussed 3…”
Section: Climate Journalists’ Professional Roles and Role Perceptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…An international survey of 592 science journalists from all continents found that 43% believed that their role was “to inform”, 23% “to translate complex material”, and 13% “to educate”; less than 10% saw thought their role entailed “mobilising or entertaining the public” or being a “public watchdog” (Bauer et al, 2013b, p. 24). The rare items of scholarship on science journalists in the Global South have generally demonstrated a “scarcity of critical science reporting” (Nguyen et al, 2020, p. 980). Similarly, a survey of more than 60 climate journalists from India, Germany, Switzerland, the US, and the UK identified the presence of a common transnational “interpretive community” in support of the mainstream consensus on anthropogenic climate change and had more traditional self‐perceptions as explainers of a complex phenomenon (Brüggemann & Engesser, 2014), although no similarities or differences between the countries were discussed 3…”
Section: Climate Journalists’ Professional Roles and Role Perceptionsmentioning
confidence: 99%
“…This is not only true in relation to the above‐mentioned featuring of skeptic sources but also regarding the proportion of foreign, international, and transnational sources in different countries’ climate‐related news (cf. Nguyen et al, 2020).…”
Section: Climate Journalists’ Relationships With Their Sourcesmentioning
confidence: 99%
“…According to Dickson (2005), democratic dialogue on science-related matters is critical for modern societies; hence, providing reliable information in an accessible manner is an essential prerequisite for this to occur. Moreover, Nguyen and Tran (2019, p. 973) argue that in developing countries, science journalism plays an almost exclusive role in informing and engaging laypeople with science and its sociocultural, economic and political implications.…”
Section: Main Features Of Today’s Media Treatment Of Sciencementioning
confidence: 99%
“…‘The organizations, the science journalists they employ, and science itself have long been comfortable with relatively superficial understandings of audience’ (Dunwoody, 2007, p. 241). Recently, much of the research into how science is communicating to broad public and what the audience thinks and feels about science reportage has been mainly conducted in West Europe (e.g., de Semir, 2010; Irwin, 2001; Scharrer et al, 2016) and Northern America (e.g., Brossard, 2013; Dunwoody, 2007; Mooney & Kirshenbaum, 2009; Szu et al, 2017) with some exceptions regarding other regions (e.g., Massarani, 2014; Nguyen & Tran, 2019). Noticeably, there is a fundamental lack of knowledge on how people in Ukraine perceive science-related matters presented by the media within local socio-historical, political and economic contexts in which they operate.…”
Section: Main Features Of Today’s Media Treatment Of Sciencementioning
confidence: 99%
“…These issues continue to be essential despite changes in the media ecology and the emergence of social media as the traditional (legacy) news media continue to be the central link between the public and science (Long 1995;Nguyen and McIlwaine 2011;Nguyen and Tran 2019). Therefore, gaps and flaws in the reporting of science news by mainstream media continue to give a detrimental effect on levels of public understanding of science.…”
Section: Introductionmentioning
confidence: 99%